Pyrolysis of Crofton weed for the production of aldehyde rich bio-oil and combustible matter rich bio-gas. (5th February 2019) - Cheng, Song; Shu, Jianhua; Xia, Hongying; Wang, Shixing; Zhang, Libo; Peng, Jinhui; Li, Chunyang; Jiang, Xin; Zhang, Qi
Highlights: Pyrolysis of Crofton weed can produce of aldehyde rich bio-oil. Bio-gas contains large amounts of combustible gas. Pyrolysis realizes comprehensive utilization of the Crofton weed. Abstract: In this work, the properties of pyrolysis products that obtained from the pyrolysis of Crofton weed was systematically researched. The effect of the different operation factors such as pyrolysis temperature, pyrolysis time, nitrogen flow rate and heating rate on the yields of three products was studied. The results showed that pyrolysis temperature and pyrolysis time have important influence on bio-oil yield, and heating rate has a decisive effect on bio-oil quality. The optimum pyrolysis condition is pyrolysis temperature of the 600 °C, heating rate of 20 °C/min, pyrolysis time of 50 min and nitrogen flow rate of 200 ml/min. The components of bio-oil and bio-gas are characterized by GC–MS and GC under optimum pyrolysis condition, respectively. The main identified compounds of bio-oils were aldehyde, phenol and ketone, corresponding to the contents of the 28.09%, 13.04% and 15.39% of the total area, respectively. Therefore, it can be used as the potential chemical materials in the food, chemical, pharmaceutical and other industries. In addition, Bio-gas mainly contains combustible gases, which accounts for as high as 82.51%. The method of the pyrolysis realizes comprehensive utilization of the Crofton weed.